REKONSTRUKSI EDUKASI: MELESTARIKAN ALAM PANDAWA MELALUI PENGOLAHAN SAMPAH PLASTIK - Ni Putu Devi Ary Santhi; Ni Putu Laras Purnamasari; I Kadek Juni Arta (Fakultas Teknik dan Informatika Universitas PGRI Mahadewa Indonesia, 2025)
Plastic waste is an urgent problem that must be addressed immediately. Plastic not only damages the ecosystem, but also threatens human health if not handled properly. As one of the efforts to overcome problems related to plastic waste, the Fine Arts Education study program (PPSR) in collaboration with the Informatics Engineering study program at PGRI Mahadewa University, carries out good activities, namely Community Service (PKM) activities. The activity program carried out is the creation of a plastic recycling installation entitled